Development of cisplatin resistance in breast cancer MCF7 cells by up-regulating aldo-keto reductase 1C3 expression, glutathione synthesis and proteasomal proteolysis. (22nd October 2021) - Kobayashi, Mio; Yonezawa, Ayano; Takasawa, Hiroaki; Nagao, Yukino; Iguchi, Kazuhiro; Endo, Satoshi; Ikari, Akira; Matsunaga, Toshiyuki
Abstract: Cisplatin (CDDP) is widely prescribed for the treatment of various cancers including bladder cancers, whereas its clinical use for breast cancer chemotherapy is restricted owing to easy acquisition of the chemoresistance. Here, we established a highly CDDP-resistant variant of human breast cancer MCF7 cells and found that procuring the resistance aberrantly elevates the expression of aldo-keto reductase (AKR) 1C3. Additionally, MCF7 cell sensitivity to CDDP was decreased and increased by overexpression and knockdown, respectively, of AKR1C3, clearly inferring that the enzyme plays a crucial role in acquiring the CDDP resistance. The CDDP-resistant cells suppressed the formation of cytotoxic reactive aldehydes by CDDP treatment, and the suppressive effects were almost completely abolished by pretreating with AKR1C3 inhibitor. The resistant cells also exhibited the elevated glutathione amount and 26S proteasomal proteolytic activities, and their CDDP sensitivity was significantly augmented by pretreatment with an inhibitor of glutathione synthesis or proteasomal proteolysis. Moreover, the combined treatment with inhibitors of AKR1C3, glutathione synthesis and/or proteasomal proteolysis potently overcame the CDDP resistance and docetaxel cross-resistance. Taken together, our results suggest that the combination of inhibitors of AKR1C3, glutathione synthesis and/or proteasomal proteolysis is effective as an adjuvant therapy to enhance CDDP sensitivity of breast cancer cells. Graphical Abstract: